On the use of combinatorial antibody libraries to clone the "fossil record" of an individual's immune response. - Lerner, R A (1991)
For about the last century the record of immunological events could only be obtained from serum proteins. We suggest that in the future this will change and the far more detailed nucleic acid record will provide new insights into immunological processes as well as selective access to the complete repertoire.